2012
DOI: 10.1007/s10555-012-9360-1
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of tumor and metastasis progression through the scaffolding functions of SSeCKS/Gravin/AKAP12

Abstract: Scaffolding proteins such as SSeCKS/Gravin/AKAP12 (“AKAP12”) are thought to control oncogenic signaling pathways by regulating key mediators in a spatiotemporal manner. The downregulation of AKAP12 in many human cancers, often associated with promoter hypermethylation, or the loss of its locus at 6q24-25.2, correlates with progression to malignancy and metastasis. The forced re-expression of AKAP12 in cancer cell lines suppresses in vitro parameters of oncogenic growth, invasiveness and cell motility through i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
85
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 74 publications
(88 reference statements)
2
85
0
Order By: Relevance
“…Like E-cadherin, P-cadherin (CDH3) expression promoted cell-cell adhesion and countered invasion in melanoma [96], oral squamous cell carcinoma [97] and breast cancer model systems [98]; HGF ligands suppressed CDH3 in PC3M, suggesting release from this negative regulator consistent with enhanced invasion. Similarly, the adhesion adapter AKAP12 repressed prostate metastasis and cell motility by sequestering Src away from FAK-associated adhesion and signaling complexes [99][100][101], suggesting that AKAP12 suppression by HGF ligands is likely to promote PC3M invasion and metastasis. HGF-suppression of the protein tyrosine phosphatase encoded by PTPRM, a negative regulator of invasion by glioma [102] and breast cancer [103] cells, and upregulation of the integrin adapter encoded by NEDD9, which promotes epithelial-to-mesenchymal transition and invasion by PCa cells [104,105], also predict enhancement of PC3M invasiveness.…”
Section: Metabolism and Ion Transport (Asns And Scnn1g)mentioning
confidence: 99%
“…Like E-cadherin, P-cadherin (CDH3) expression promoted cell-cell adhesion and countered invasion in melanoma [96], oral squamous cell carcinoma [97] and breast cancer model systems [98]; HGF ligands suppressed CDH3 in PC3M, suggesting release from this negative regulator consistent with enhanced invasion. Similarly, the adhesion adapter AKAP12 repressed prostate metastasis and cell motility by sequestering Src away from FAK-associated adhesion and signaling complexes [99][100][101], suggesting that AKAP12 suppression by HGF ligands is likely to promote PC3M invasion and metastasis. HGF-suppression of the protein tyrosine phosphatase encoded by PTPRM, a negative regulator of invasion by glioma [102] and breast cancer [103] cells, and upregulation of the integrin adapter encoded by NEDD9, which promotes epithelial-to-mesenchymal transition and invasion by PCa cells [104,105], also predict enhancement of PC3M invasiveness.…”
Section: Metabolism and Ion Transport (Asns And Scnn1g)mentioning
confidence: 99%
“…Following crosslinking to the actin cytoskeleton and plasma membrane, SSeCKs translocates and correspondingly transports macromolecules such as Src, PKC, PKA, Factin, calmodulin, cyclins and phospholipids to other organelles. SSeCKS re-expression decreases invasion and invadosome formation by disengaging Src from activating downstream RhoGTPase and/or PKC-Raf/MEK/ ERK-mediated pathways which, in turn, control MMP expression [97][98][99].…”
Section: Raf Kinase Inhibitor Protein (Rkip)mentioning
confidence: 99%
“…Gelman and colleagues have shown that SSeCKS re-expression in rat prostate cancer cells reduces metastasis by affecting neovascularization at distal sites, but not by inhibiting tumor cell motility or proliferation [97,100,101]. Using a spontaneous metastasis model, Akakura et al showed that B16F10 melanoma cells developed significantly more metastases in SSeCKS-null mice with no difference on primary tumor growth [102].…”
Section: Raf Kinase Inhibitor Protein (Rkip)mentioning
confidence: 99%
“…Six out of seven published reports indicate AKAP12 plays a role in cell proliferation [145,152,[156][157][158][159][160]. Early passaged AKAP12 -/-or knock out MEFs cells exhibited a higher cellular proliferation than wild type MEFs [158].…”
Section: Akap12 Is a Direct Target Of Mir-186 In Metastatic Pcamentioning
confidence: 99%
“…Only a select number of miR-186 targets (p53, PTEN, CASP9, FOXO3, AKAP12, PTEN, TRIB3, IL1RL1) AKAP12 (A-kinase anchor protein 12) also known as the mouse homolog SSecKS functions as a scaffold protein in signal transduction that associates with protein kinases A (PKA) and C and phosphatase [152].…”
Section: Akap12 Is a Direct Target Of Mir-186 In Metastatic Pcamentioning
confidence: 99%